Pengaruh Pembawa Acara terhadap Minat Menonton dalam Komunitas (Survei Talkshow Tonight Show pada Komunitas Tonight Mania) - Marselinus Chandrajaya Putra; Muhammad Gafar Yoedtadi (Koneksi, 2021)
Presenter is a person whose job is to bring and convey information, or a narrative in a television program. Interest is defined as a feeling of liking or pleasure as well as feeling attracted to an object or activity without instructions and usually there is a tendency to look for the object that you like. Tonight Show is a NET TV talk show hosted by four presenters. This study uses a quantitative approach with a survey method. Data collection using a questionnaire distributed to respondents who are members of the Tonight Mania community Whatsapp group. Based on the research that has been done, it is found that there is a strong influence from the Tonight Show host on the interest in watching the Tonight Show program in the Tonight Mania Community. This is shown by the results of the correlation coefficient test of 0.691 and the influence of 47% obtained from the results of the coefficient of determination test. Based on simple linear regression testing, the results show that the Tonight Show host gives a positive value to the interest in watching the Tonight Show program in the Tonight Mania community, and based on the results of the t test, the results show that Ho is rejected and Ha is accepted.Presenter adalah orang yang bertugas untuk membawakan serta menyampaikan sebuah informasi, atau narasi dalam sebuah program televisi. Minat diartikan sebagai rasa suka  atau  senang serta rasa tertarik terhadap suatu objek atau aktivitas tanpa adanya suruhan dan biasanya muncul kecenderungan untuk mencari objek yang disenangi tersebut. Tonight Show merupakan sebuah acara talkshow NET TV yang dipandu oleh empat pembawa acara. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Pengumpulan data menggunakan kuesioner yang disebar kepada responden yang tergabung dalam grup Whatsapp komunitas Tonight Mania. Berdasarkan peneltian yang telah dilakukan, didapatkan hasil bahwa terdapat pengaruh yang kuat dari pembawa acara Tonight Show terhadap minat menonton acara Tonight Show pada Komunitas Tonight Mania. Hal itu ditunjukan dari hasil uji koefisien korelasi sebesar 0,691 serta adanya pengaruh sebesar 47% yang didapatkan dari hasil uji koefesien determinasi. Berdasarkan pengujian regresi linear sederhana didapatkan hasil bahwa pembawa acara Tonight Show memberikan nilai positif terhadap minat menonton acara Tonight Show pada komunitas Tonight Mania, serta berdasarkan hasil dari uji t didapatkan hasil bahwa Ho ditolak dan Ha diterima.